STAGES OF FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS BY MEANS EXTRACURRICULAR WORK OF HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
The article shows the advantage of stage by stage forming comunicative culture, revels the contents of each stage.
Keywords: 1